If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 13(n + 4 + 7n) = 0 Reorder the terms: 13(4 + n + 7n) = 0 Combine like terms: n + 7n = 8n 13(4 + 8n) = 0 (4 * 13 + 8n * 13) = 0 (52 + 104n) = 0 Solving 52 + 104n = 0 Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '-52' to each side of the equation. 52 + -52 + 104n = 0 + -52 Combine like terms: 52 + -52 = 0 0 + 104n = 0 + -52 104n = 0 + -52 Combine like terms: 0 + -52 = -52 104n = -52 Divide each side by '104'. n = -0.5 Simplifying n = -0.5
| -9(v-6)=7v+22 | | 5x+8-x=24 | | 10(-4-3x)=-130 | | n-30=17+14 | | -7x+34=-3(x-2) | | n-7=3n | | x+3.5=18.2 | | -6p+6= | | -36+(-12)=7(-12)+2(-12) | | 16a=30 | | 9.95+3.59s=33.44 | | 9(x-3)=7x-31 | | x-3.5=18.2 | | 5n^2+19n-66=0 | | 4(5+2x)-5=3(3x+7)77 | | SA=2pirh | | 6x+4x-36=90-8x | | x^2-4x=6y-28 | | x+3x=13 | | 1.3+4x-2.8=0.3 | | 1.3+4x-2.8=0.3 | | x+3x=13 | | x+162=388whatisx | | 14-5x=-22-x | | 4a+23-9=21 | | 4x+9=3(x-7)-8 | | 4x+9=3(x-7)-8 | | -13t+18=-15t | | 15q-5q=-5 | | -13t+18=-15t | | 4a+23-9a=21 | | 110=143.49+0.98m |